China : Financial Sector Assessment - World Bank; International Monetary Fund (World Bank, Washington, DC, 2013)
This report summarizes the findings of the Financial Sector Assessment Program (FSAP) exercise for China undertaken in 2010 by a joint International Monetary Fund (IMF) and World Bank team. The first mission (June) assessed the observance of selected international standards and codes, and initiated discussions on a broad range of financial sector issues. The second mission (December) completed its review and presented a draft Aide-Memoire along with draft technical and background notes covering a range of topics relevant to China's financial sector. This report points out near-term risks, reform challenges and development opportunities China confronts as it continues to modernize its financial sector. China faces potential vulnerabilities, near-term risks and policy-induced distortions common to an evolving financial system. The challenges and opportunities are not unique, and can be addressed. The author proposes that the authorities could consider carefully sequencing the following reforms and development options: (i) further deepening the commercial orientation of the financial system; (ii) moving to more market-based means of controlling monetary and financial conditions; (iii) further strengthening regulation and supervision; (iv) upgrading the framework for financial stability and crisis management; (v) revising the strategy for financial inclusion to achieve improved access to financial services ; (vi) continuing steps to support a broad based capital market; and (vii) continue to strengthen and deepen the insurance and pension sectors; and (viii)continue enhancement of the financial market infrastructure.